CULT OF THE BODY, AESTHETICS AND CONTROL (Fiep Bulletin - online, 2015)
This study aims at identifying the ideas of teachers and students of Physical Education about the corporality issues before the ever-growing demands of perfect bodies. The study was based on eight undergraduate papers for Physical Education courses at universities of Rio de Janeiro. Authors such as Goldenberg (2004), Elias (1999), Vilaça (1999), Perniola (1998), Lacerda (2004), and others were used as theoretical references. Each of the consulted papers was presented as an explorative and descriptive study, with data collected via questionnaires. It was observed that there is a major concern with good shape, which, in Elias' view, seems to be a significant control and moralizing factor.
Keywords: body; aesthetics; control.